Influence of playing style on the physiological responses of offensive players in table tennis - Martin, C.; Favier-Ambrosini, B.; Mousset, K.; Brault S.; Zouhal, H.; Prioux, J. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The study aimed to analyse the influence of playing style on the physiological responses of offensive players and on match characteristics during table tennis matches.